(3OQGSI ebGQfIs - (3SdWGf YHO Gddg eMehO(B, (3GdLhGQjs ((3HjQhJ(B:s (3efThQGJ GdMdHj GdMbhbjI(B,s, 2010)
(3bGYOI NVhY GdYbO dbGfhf GdEOGQj, GdbGfhf GdhGLH GdJWjSb Ydi GdMSGH GdLGQj, GdbGfhf GdhGLH GdJWHjb Ydi GdEYJeGO GdeSJfOjs
(3HHdjhZQGajG(B: (3U(B.177-188s
Keywords: (3GdEYJeGOGJ GdeSJfOjIs; (3GdHfhcs; (3GdYbhOs